Professional Information Technology Teacher Content And Essence Of Competence Development - Avloqulov Jamoliddin Bahriddinovich (Journal of Learning on History and Social Sciences, 2024)
This article describes the modern requirements for teachers of future technological education, the development of information acquisition competence as a pedagogical problem, and the motivations for its development.